2000
DOI: 10.1080/00071660086448
|View full text |Cite
|
Sign up to set email alerts
|

Effect of food enzymes on utilisation of lupin carbohydrates by broilers

Abstract: 1. The effects of 3 commercial enzyme products on the nutritive value of 2 lupin species were investigated with the emphasis on changes in composition of non-starch polysaccharides (NSPs) along the digestive tract. Enzyme A contained primarily cellulase, beta-glucanase and xylanase activities, enzyme B primarily hemicellulase, pentosanase and xylanase activities, and enzyme C primarily hemicellulase, pectinase and beta-glucanase activities. 2. The enzymes were added to semi-purified diets based on sorghum and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 19 publications
2
33
0
Order By: Relevance
“…The carbohydrate reserves in white lupins were the NSP. White lupins contained 355 to 370 g/kg total NSP, which is in agreement with those reported by Kocher et al (2000). The high contents of soluble NSP (29 to 50 g/kg DM) determined in white lupins can be a concern in poultry nutrition and may have implications for digesta viscosity and nutrient utilisation in birds (Smits and Annison, 1996).…”
Section: Discussionsupporting
confidence: 88%
“…The carbohydrate reserves in white lupins were the NSP. White lupins contained 355 to 370 g/kg total NSP, which is in agreement with those reported by Kocher et al (2000). The high contents of soluble NSP (29 to 50 g/kg DM) determined in white lupins can be a concern in poultry nutrition and may have implications for digesta viscosity and nutrient utilisation in birds (Smits and Annison, 1996).…”
Section: Discussionsupporting
confidence: 88%
“…The significant enlargement of the liver in birds fed yellow lupin diets in comparison with narrow-leafed ones may confirm this conclusion. Kocher et al (2000) reported that the ileal protein digestibility of narrow-leafed lupin was about 0.85, while jejunal and ileal NSP digestibilities were 0.03 and 0.12, respectively. This proved that neither were lupin NSP digested in the upper part nor were they fermented in the lower part of the small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Emir determined by Steenfeldt et al (2003), 11.6 mPas·s on the diet containing 35% narrow-leafed lupin cv. Gungurru measured by Kocher et al (2000), or 32.7 mPas·s on the diet containing 40% narrow-leafed lupin, vs the 3.5 mPas·s on the diet containing 40% yellow lupin measured by Olkow ski et al (2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations